Foreign and security policy in the program principles of the Ukrinian political parties / Piotr Bajor. - Bajor, Piotr (1981- ).
People's Front, Petro Poroshenko Bloc, All-Ukrainian Self-Reliance Association, Opposition Bloc, Radical Party of Oleh Lyashko, All-Ukrainian Union Batkivshchyna.